Does Inovative Use of Social Media Training Enhance Business Growth? A Case of Subira Self Help Group, Nairobi - Misango, Sedina (Machakos University, 2018)
The general purpose of this study was to investigate the role of innovative entrepreneurial training programs on business growth among Subira Self-help group Nairobi. The innovative training included use of smart mobile phones to conduct business and market products, use of social media to reach customers and advertising of products by use of mobile phone technology. The study used a descriptive research design approach. The study sample was all the 48 members of the Self-help business group. A research questionnaire was used to collect the data. Descriptive statistics techniques were used to analyze the quantitative data. The researcher conducted regression analysis on the dependent variable aspect of business growth and the independent variable aspects of innovative business training programs (use of social media). According to the ANOVA results, the aspect of the independent variable was found not to be significant towards business growth represented by p- value of 0.324. We therefore accept the null hypothesis and conclude that business growth does not depend on innovative social media training.The study found that a unit increase in social media training programs led to an increase in business growth penetration by a factor of 0.146 but is weak.The study concluded that various types of business training programs were responsible for the business growth. The study therefore recommends that there is need for the members of the group to adopt and equip themselves with modern use of phone technology and applications that can grow businesses but still adopt other factors of business growth in the market. They should also be ready to be trained by field officers and colleagues on those programs that enhance business growth; since such programs portray positive impact towards business growth. Keywords: Business growth, Innovation, Mobile phone technology, Training program, Social media, Self-help group.
Keywords: Business growth; Mobile phone technology